2009
DOI: 10.1123/ijsnem.19.2.172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein-Supplement Timing on Strength, Power, and Body-Composition Changes in Resistance-Trained Men

Abstract: The effect of 10 wk of protein-supplement timing on strength, power, and body composition was examined in 33 resistance-trained men. Participants were randomly assigned to a protein supplement either provided in the morning and evening (n = 13) or provided immediately before and immediately after workouts (n = 13). In addition, 7 participants agreed to serve as a control group and did not use any protein or other nutritional supplement. During each testing session participants were assessed for strength (one-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 27 publications
2
82
2
3
Order By: Relevance
“…In general, protein supplements have been shown to improve physical performance before and after training (Hoffman et al, 2009;Josse et al, 2010).lean body mass (Cribb & Hayes 2006;Josse et al, 2010). On the other hand, specific gains vary according to the type and amount of proteins (Hoffman et al, 2009;Andersen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, protein supplements have been shown to improve physical performance before and after training (Hoffman et al, 2009;Josse et al, 2010).lean body mass (Cribb & Hayes 2006;Josse et al, 2010). On the other hand, specific gains vary according to the type and amount of proteins (Hoffman et al, 2009;Andersen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, specific gains vary according to the type and amount of proteins (Hoffman et al, 2009;Andersen et al, 2005). While the usage rate of ergogenic products according to the educational level of female weightlifters is not changed, this ratio varies significantly between secondary school, high school and university graduates (Fischer's exact p value=.024, p<0.05) in males (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…For a few years, these results were strongly considered as evidence that nutrient timing was a favorable strategy to optimize widespread positive adaptations to resistance training. In 2009, Jay Hoffman and his team of investigators published a near-identical study using trained collegiate athletes and reported that no differences in performance or body composition were observed between the group of athletes ingesting protein timed close to each workout and the group of athletes consuming identical nutrients in the morning and evening of training days [ 62 ]. A closer analysis of this research highlighted the fact that the study participants in the Hoffman study were already ingesting a level of daily protein that met current protein recommendation for strength and power athletes [ 63 ], while the participants in the Cribb study were ingesting less than the recommended amounts.…”
Section: Proteinmentioning
confidence: 96%
“…La mayor parte de los estudios que han analizado el balance de nitrógeno en colectivos deportivos señalan que la ingesta óptima de proteínas para alcanzar el máximo desarrollo muscular se sitúa en 1,7-1,8 g/kg (alrededor del 225% de la ingesta recomendada (IR) en personas sedentarias) 3,54 , y concluyen que cantidades superiores a 1,8 g/kg de peso corporal no han demostrado tener mayor bene cio en el aumento de la masa muscular de los deportistas de fuerza 55 . En este sentido, los trabajos de Nicholas A. Burd 3 y Jay R. Hoffman 54 coinciden al concluir que, al consumir dietas que aportan más de 2,4 g de proteínas por kg de peso corporal, se aumenta la oxidación de AA sin que se observe un incremento adicional de biosíntesis proteica, aun con un entrenamiento adecuado de fuerza. Otros autores señalan también que no es necesario más de 2 g de proteínas por kg de peso corporal al día, ya que no presenta ningún bene cio frente a dietas con un contenido menor [56][57][58] .…”
Section: Grupounclassified
“…Por ejemplo, las necesidades proteicas para dos deportistas de fuerza de 90 kg de peso que di eran en sus porcentajes de masa muscular no deberían ser iguales, debido a que el individuo con un mayor porcentaje de masa muscular requerirá supuestamente de un mayor aporte de proteínas para mantener el estado anabólico que el de menor tejido muscular. Pese a que no se han encontrado muchos estudios que contemplen este aspecto, en dos estudios se concluye que la ingesta óptima de proteínas para alcanzar el máximo desarrollo muscular se sitúa en 3,3-3,4 g de proteínas por kg de masa muscular 3,54 . Por lo tanto, desde el punto de vista dietético-nutricional, es importante conocer cuáles son los objetivos del entrenamiento (si el trabajo prioritario que realizar es de resistencia aeróbica o fuerza) para poder realizar un asesoramiento preciso basado en las necesidades proteicas.…”
Section: Grupounclassified